A Literature Review: Is Transformational Leadership Elitist and Antidemocratic? - Fredson Kotamena; Pierre Senjaya; Agustian Budi Prasetya (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
In this study we aim to explore and determine whether transformational leadership is elitist and anti-democratic. In order to see the link with transformational leadership, we organize a literature review to locate relevant literature and extract knowledge about elitism and democratic leadership. Researcher found transformational leadership is not elitist and anti-democratic. It’s empowering the employee to encouraging inspiration, idealized power, intellectual stimulation and individual judgment. It engages workers through participatory, support for new ideas and a substantial degree of flexibility and autonomy for be pro-active and take risks, also rely heavily on communication and relationships. This research only to find out whether transformational leadership is indeed elitist and anti-democratic based on a literature review and for empirical evidence further study is needed. The relation between transformational leadership and member responses to organizational change has been empirically validated by numerous studies.